Gold catalysts prepared by ion exchange for use in ethylene glycol oxidation: An exploratory study - Case, Jennifer Margaret (Department of Chemical Engineering, 2014)
Heterogeneous catalysis using supported gold nanocrystallites has attracted increasing attention over the last two decades for its applicability to a wide range of reactions, offering activity under ambient conditions, as well as high selectivities towards particular products. This study focuses on a relatively uncommon method of gold catalyst preparation, ion exchange, which involves the suspension of the support in a solution containing cationic or anionic gold complex precursors at a fixed pH, followed by separation of the solid catalyst from this solution, drying and calcination. Theoretically, ion exchange preparation offers the possibility of highly dispersed gold crystallites, which are desirable in gold catalysis. A series of catalysts was prepared using both anionic and cationic exchange, with [AuCl4]- and [Au(NH3)4]3+ respectively as gold precursors, with such solution concentrations that maximum loadings in the region of 3 to 4 wt-% Au could be obtained. Activated carbon and Î³-alumina were used as supports. Catalysts were prepared at different pHs theorised to influence electrostatic adsorption differentially. Calcination was conducted at 300ÂºC in hydrogen. Gold loading was established using Atomic Absorption Spectroscopy (AAS) and Thermogravimetric Analysis (TGA). Loading to full capacity was noted in a number of instances with the carbon supported catalysts. Most of the gold uptake took place in the first two hours of aging. In many but not in all cases higher loadings were noted at pHs further away from the iso-electric point (IEP), in the region where the support is oppositely charged to the complexed gold ion, thus confirming the electrostatic adsorption theory for ion exchange. The size of gold crystallites was determined using Transmission Electron Microscopy (TEM), X-Ray Diffraction (XRD) and oxygen chemisorption. TEM results were used to calculate average crystallite sizes as well as to give an indication of size distributions. Measurable XRD gold peaks were only visible for supported carbon catalysts, and the crystallite sizes estimated using this technique were notably lower than average crystallite sizes from TEM for these catalysts. The carbon supports showed a large uptake of oxygen in the chemisorption process, and thus this technique was only used as a method for crystallite size determination for alumina supported catalysts. These crystallite sizes showed general iii agreement with the average sizes derived from TEM. In summary, the carbon supported catalysts had average crystallite sizes greater than 10 nm with wide size distributions, while the alumina catalysts had average crystallite sizes nearly all under 10 nm and narrow size distributions. Ethylene glycol oxidation under atmospheric pressure was employed as a test reaction, using 0.05 M ethylene glycol at a temperature of 60 ÂºC and at a pH of 11. Only the alumina supported catalysts displayed activity under these conditions, with initial reaction rates in the range of 2 to 15 mmol EG / g Au . min which are comparable to those reported in the literature. Across the range of crystallite sizes represented in these catalysts there was no evidence of dependency of activity on crystallite size.